2010
DOI: 10.1016/j.avsg.2010.02.044
|View full text |Cite
|
Sign up to set email alerts
|

Successful Endovascular Infrarenal Aneurysm Repair in a Patient With Situs Inversus Totalis

Abstract: Situs inversus totalis is a rare autosomal recessive developmental anomaly. There are very few reports in the published literature of abdominal aortic aneurysm in patient with situs inversus totalis, all of whom underwent open aneurysm repair. This is the first case in the world's literature to describe a patient with situs inversus totalis who had a successful endovascular infrarenal aneurysm repair. Although endovascular infrarenal aneurysm repair should not be more challenging, the endovascular approach may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 5 publications
0
10
0
3
Order By: Relevance
“…9 Recently, Chan et al reported a case of endovascular AAA repair in a patient with SIT, demonstrating the feasibility of an endovascular approach. 6 We believe our report to be the first to document the repair of a juxtarenal AAA in SIT through a retroperitoneal approach.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…9 Recently, Chan et al reported a case of endovascular AAA repair in a patient with SIT, demonstrating the feasibility of an endovascular approach. 6 We believe our report to be the first to document the repair of a juxtarenal AAA in SIT through a retroperitoneal approach.…”
Section: Discussionmentioning
confidence: 68%
“…The presence of AAA in situs inversus is uncommon, with only a small number of case reports describing this condition. [5][6][7][8][9] Consequently, the ideal surgical approach in a patient with SIT and AAA is unknown. Kimura et al described performing a right-sided thoracotomy with proximal aortic cross-clamping to gain vascular control in a patient with SIT and aneurysmal rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Coexistence of abdominal aortic aneurysm and SIT is extremely rare, so its prevalence has never been estimated, because only seven cases have been reported [4–10] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently Chan et al [9] reported the first case of exclusion of AAA using elective endovascular procedure in a patient with high surgical risk and SIT and achieved a satisfactory result.…”
Section: Discussionmentioning
confidence: 99%
“…La presentación de aneurismas de aorta abdominal (AAA) en pacientes con SIT es infrecuente en la literatura; se identifican pocos reportes en las bases de datos disponibles [3][4][5][6][7][8][9] . La presentación de un AAA en un paciente con SIT no necesariamente implica mayor morbimortalidad, pero su rotura se asocia a un mayor riesgo de complicaciones 4 .…”
Section: Introductionunclassified